Effects of Brazilian and Bulgarian propolis on bactericidal activity of macrophages against Salmonella Typhimurium - Orsi, Ricardo de Oliveira [UNESP]; Sforcin, J. M.; Funari, SRC; Bankova, N. (Elsevier B.V., 2005)
Propolis has been used in folk medicine since ancient times due to its, many biological properties: such as antimicrobial. antinflammatory, antioxidant, immunomodulatory activities, among others. 'Macrophages play an important role in the early phase of Salmonella infection. In this work, macrophages were prestimated with Brazilian or Bulgarian propolis and subsequently challenged with Salmonella Typhimurium at different macrophage/bacteria ratio. After 60 min of incubation. cells were harvested with Triton-X to lyse the macrophages. To assess the bactericidal activity. The number of colony-forming units (CFU) of S. typhimurium was determined by plating 0.1 mL in 'Mueller Hinton agar. After 24 h. CFU were counted. and the percentage of bactericidal activity was obtained. Propolis from Brazil and Bulgaria enhanced the bactericidal activity of macrophages, depending on its concentration. Brazilian propolis seemed to be more efficient than that from Bulgaria. because of their different chemical composition. In Bulgaria, bees collect the material mainly from the bud exudate of poplar tree, while in Brazil, Baccharis dracunculifolia DC. was shown to be the main propolis source. Our data also showed that the increased bactericidal activity of macrophages involved the participation of oxygen (H2O2) and nitrogen (NO) intermediate metabolites. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: propolis; macrophages; hydrogen peroxide; nitric oxide; Brazil; Bulgaria